A nurse-led 'first fitter' clinic in a paediatric emergency department: an experience. Issue 2 (15th February 2010) - Williams, Kim; Appleton, Richard; Stewart, Briar; Sweeney, Anne
Abstract : Background: The diagnoses of a child who presents to an Accident and Emergency (A&E) department with 'jerking' or loss of consciousness include an epileptic seizure, vasovagal event, cardiac syncope or other paroxysmal event. Where the likely diagnosis is a first epileptic tonic-clonic seizure, there is no consensus on how these children should be followed-up. This is important as many parents of children who experience an epileptic tonic-clonic seizure will be anxious and concerned about a recurrence and what to do if it does. A first fitter clinic (FFC) was established in the Accident and Emergency Department of our hospital to standardise the management of these children. Methods: Children presenting to the A&E department of a large children's hospital considered to have had a first tonic-clonic epileptic seizure were offered an appointment for the FFC within 3  weeks of their attendance. The clinic was supervised by an advanced nurse practitioner. Details of the child's reported tonic-clonic seizure were recorded on to a standardised proforma and additional information was obtained on other paroxysmal epileptic and non-epileptic events. Results: Altogether, 120 children were offered an appointment in the FFC, of which 117 (97%) attended. Their mean age was 9.5 (range: 3.5–15.2)years. Following review in the clinic, 82 (70.1%) of the 117 children were considered to have experienced an epileptic tonic-clonic seizure. Twenty-eight patients were considered to have had a vaso-vagal attack or reflex anoxic seizure; two, a possible cardiac arrhythmia; two a breath-holding episode and in three patients the events could not be classified. Conclusion: The FFC was well-attended suggesting that families appreciated early follow-up and the opportunity to address their concerns and provide advice about what to do if there was a recurrence. The study also demonstrated that approximately one-third of children were misdiagnosed as having experienced a tonic-clonic seizure.